Pengaruh Dampak Boikot Produk Amerika Terhadap Perokonomian Indonesia - Oktavia, Oktavia; Muhammad Riziq Noval; Rizka Hanipah; Melani Fitriya Handayani (Pusat Riset dan Inovasi Nasional, 2024)
Plans to boycott American products must take into account the national economy. American products help drive economic growth, because Indonesia's population and management of natural resources depend on American products. Boycott actions suppress economic growth by reducing demand and increasing unemployment. Moreover, on the one hand, this step will have no effect because economic relations between Indonesia and the United States are legalized by regional and international trade organizations. The method used to analyze is a qualitative method.